2019
DOI: 10.1002/cctc.201900924
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Based Catalyst Supported on Different Morphologies of Alumina for Non‐oxidative Propane Dehydrogenation: Effect of Metal Support Interaction and Lewis Acidic Sites

Abstract: Developing an economically viable and eco-friendly catalyst is essential for the dehydrogenation reaction. In this context, cobalt-based catalysts supported on different morphologies of γ-Al 2 O 3 , nano-sheet (Al 2 O 3 À NS), nano-fiber (Al 2 O 3 À NF) and nanoplate (Al 2 O 3 À NP) were synthesized using wetness impregnation method and tested for non-oxidative propane dehydrogenation reaction. Metal support interaction and Lewis acidic center play a crucial role in propane dehydrogenation reaction; therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…Propylene is one of the most important feedstocks in the global economy for the production of various chemicals and fuels 1–4 . The worldwide increasing demand of propylene together with the increasing availability of propane from clean energy source as shale gas has spurred interest in on‐purpose production of propylene via direct dehydrogenation 5–9 . Pt‐based catalysts are widely used in industrial propane dehydrogenation (PDH) processes because of their superior activation of paraffinic CH bonds and low activity to CC cleavage 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Propylene is one of the most important feedstocks in the global economy for the production of various chemicals and fuels 1–4 . The worldwide increasing demand of propylene together with the increasing availability of propane from clean energy source as shale gas has spurred interest in on‐purpose production of propylene via direct dehydrogenation 5–9 . Pt‐based catalysts are widely used in industrial propane dehydrogenation (PDH) processes because of their superior activation of paraffinic CH bonds and low activity to CC cleavage 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 TPD was carried out to study the adsorption/desorption of CO 2 on different catalysts, the desorption curves in Figure 6 showed that all samples contained two overlapped peaks from100 to 200, and from 200 to 600 °C, which could be attributed to the adsorption of CO 2 on weak (peak 1) and medium (peak 2) basic sites, [22a,34] respectively. The quantified results in Table S3 showed the gradually decreasing trends of CO 2 uptake as the SiO 2 content increased whatever for weak or medium basic sites.…”
Section: Resultsmentioning
confidence: 99%
“…However, operation with non‐noble‐metal catalyst like VO X /Al 2 O 3 and VO X /ZrO 2 leads to a conversion below ≈25 % and a propene selectivity below ≈90 % even at ≈600 °C, while it suffers from serious coke deposition and conversion drop in dozens of minutes [14–17] . For non‐noble metal catalyst, the lack of catalytic activity gives rise to a limited propane conversion at reduced temperatures while the complicated functional groups at surfaces distract the main reaction to generate by‐products including methane, ethane and coke [18] . The high density of weak Lewis acid sites on the surface of catalyst is beneficial for the propane dehydrogenation reaction and could suppress the cracking reaction to avoid carbon deposition [16, 19, 20] …”
Section: Figurementioning
confidence: 99%